Efektivitas Agens Hayati Biohara pada Tanaman Padi Varietas Ciherang - Rahmad Fadli; Suwandi; Nisa Ul Mardiyah (Fakultas Pertanian, Peternakan dan Perikanan Universitas Muhammadiyah Parepare, 2026)
The increasing demand for environmentally friendly agricultural systems presents challenges and opportunities for the development of sustainable rice cultivation in the lowland swamps of South Sumatra. This study aims to evaluate the effectiveness of biohara in increasing the resistance of the Ciherang rice variety to biotic and abiotic stress during the vegetative phase. Biohara itself is made from various materials such as biofertilizer and animal manure compost. This application is the first study in a lowland swamp ecosystem. The research location is in the Ogan Ilir area of Kotadaro I Village. This initial study was conducted to observe pest and disease attacks as well as growth factors such as the number of tillers and plant height. The results of the study showed a significant increase in plant growth, with an average of 44.88 cm and 38 tillers per 10 clumps. Observations of pest attacks found 11 species of insect pests from four orders, but their populations remained under control. The intensity of leaf blast disease increased gradually but remained within tolerable limits. Nitrogen, phosphorus, and potassium content in the soil increased without causing chemical imbalance. This study shows that the Biohara-based approach is not only environmentally friendly but also effective in maintaining the stability of agricultural ecosystems in vulnerable peat swamp ecosystems. This study reinforces the potential of environmentally friendly cultivation technologies as a sustainable alternative in peat swamp ecosystems.